2008
DOI: 10.2202/1542-6580.1610
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Fluidized Bed Electrode

Abstract: The present investigation attempts to study the hydrodynamic characteristics of the fluidized bed electrode. A core-annular flow model with a transfer of particles between core-annular layers has been proposed to describe the flow behavior of conducting particles in the fluidized bed electrode. The effect of individual parameters on the rate of the particle transfer across the layer and thickness of the core-annular has been critically examined and the model simulation has been verified with the data reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…These feature solid catalyst particles held in suspension by an upward gas or liquid flow stream, providing excellent catalyst interaction and mixing for electrochemical reactions. 96 Although fluidised bed reactors suffer from poor electrical contact, they removed the assumption that an electrochemical cell has to have two parallel electrodes. A recent paper demonstrated that improved electrical contact was made using magnetisable electrode particles under the influence of a magnetic field.…”
Section: Examples Of Reactor Designs and Their Performancementioning
confidence: 99%
“…These feature solid catalyst particles held in suspension by an upward gas or liquid flow stream, providing excellent catalyst interaction and mixing for electrochemical reactions. 96 Although fluidised bed reactors suffer from poor electrical contact, they removed the assumption that an electrochemical cell has to have two parallel electrodes. A recent paper demonstrated that improved electrical contact was made using magnetisable electrode particles under the influence of a magnetic field.…”
Section: Examples Of Reactor Designs and Their Performancementioning
confidence: 99%
“…Drying is a process related to reduction of moisture content of a solid matter by evaporation, blowing or heating at moderate temperature at normal or vacuum pressure [8]. Fluidized bed dryer is applied in many industries, such as mining, food, chemical and pharmaceutical industries [9]. The solid material used in drying process can be existed as powder, granules, crystals, plant seeds and even as slurry, paste, and suspension [6].…”
Section: Introductionmentioning
confidence: 99%
“…Fluidization is a technique by which fine solids are contacted with fluid (gas, liquid, or mixture of both) to transform into a fluid‐like state for the purpose of high mass transfer and heat transfer between phases. Ascribed to its high mass transfer coefficient, well contact among reactants and large electrode area, fluidized bed electrode (FBE) had been widely used in chemical process industry, such as fermentation, metallurgy, energy conversion, and wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%